José Carlos Castañeda Reyes, Egipto contemporáneo: economía, política y sociedad, México, El Colegio de México, 2011, 235 pp. - Marín Guzmán, Roberto (El Colegio de México, 2013)
José Carlos Castañeda Reyes, Egipto contemporáneo: economía, política y sociedad, Mexico, El Colegio de México, 2011, 235 pp.